L’autonomisation des Églises baniwa. Genèse et institutionnalisation d’un mouvement évangélique amérindien (Amazonie brésilienne) - Élise Capredon (Journal de la Société des Américanistes)
Since the 1990s, many studies have addressed the modes in which Amazonian indigenous people appropriate Christianity. Most of them have stressed that Amerindian conversions are generally ephemeral or “inconstant.” The case study of the Baniwa, an indigenous group of the Brazilian Amazon, reveals on the contrary the emergence of a long-lasting Amerindian Christian movement in the Upper Rio Negro region. The Baniwa, an Arawak-speaking people, have converted to evangelicalism, since the mid-20th century. Since then, they have created their own churches, in which they worship and celebrate ceremonies in the native language. By retracing the genesis and institutionalization of this movement, we aim to show that the members of this group are no longer appropriating an exogenous religion but produce now their own Christian model, founded on specific values and practices. As a conclusion, we will discuss the scope of this phenomenon.